Optimizing Exciton and Charge-Carrier Behavior in Thick-Film Organic Photovoltaics: A Comprehensive Review - Wei, Lu; Yang, Yaxin; Zhan, Lingling; Yin, Shouchun; Chen, Hongzhen (Nano-Micro Letters, 2025)
Organic photovoltaics (OPVs) have achieved remarkable progress, with laboratory-scale single-junction devices now demonstrating power conversion efficiencies (PCEs) exceeding 20%. However, these efficiencies are highly dependent on the thickness of the photoactive layer, which is typically around 100 nm. This sensitivity poses a challenge for industrial-scale fabrication. Achieving high PCEs in thick-film OPVs is therefore essential. This review systematically examines recent advancements in thick-film OPVs, focusing on the fundamental mechanisms that lead to efficiency loss and strategies to enhance performance. We provide a comprehensive analysis spanning the complete photovoltaic process chain: from initial exciton generation and diffusion dynamics, through dissociation mechanisms, to subsequent charge-carrier transport, balance optimization, and final collection efficiency. Particular emphasis is placed on cutting-edge solutions in molecular engineering and device architecture optimization. By synthesizing these interdisciplinary approaches and investigating the potential contributions in stability, cost, and machine learning aspects, this work establishes comprehensive guidelines for designing high-performance OPVs devices with minimal thickness dependence, ultimately aiming to bridge the gap between laboratory achievements and industrial manufacturing requirements. Highlights: 1 Research progress summary: Provides a systematic review of recent advancements in thick-film organic photovoltaics (OPVs) with a focus on molecular design and device engineering strategies. 2 Efficiency enhancement strategies: Explores the mechanisms limiting efficiency in thick-film devices, analyzes exciton and charge-carrier dynamics, and identifies effective approaches to improve device performance. 3 Industrialization contributions and outlook: Summarizes the potential contributions of thick-film OPVs to industrial applications and offers insights into future development directions (in stability, cost, and machine learning aspects).